Test Stability Of Natural Color Dyes From The Lether Fruit Of Palm’s Waste - Broto, R.T.D. Wisnu; Supriyo, Edy; Pudjihastuti, Isti; Arifan, Fahmi (METANA, 2018)
The leather fruit of palm (Borassus flabilifer) is one of the local fruit native to Indonesia produced from palm plants are very abundant due to not knowing the season During this leather palm fruit  is still not widely used and is only regarded as wastes. The leather palm fruit  color has anthocyanin substances which are natural pigments reddish color. The extraction of the leather palm  by using different types of solvents include water, ethanol water mixture, the mixture of water - propanol, a mixture of water-ethanol-propanol, ethanol, a mixture of ethanol - propanol and propanol. The best extraction results were obtained by using ethanol solvent. Furthermore, stability test of pigment extract’s the leather fruit of palm (anthocyanin) to pH, temperature, light, and color was done by using UV-Vis spectrophotometer at maximum wavelength 520 nm. In the stability test of pigment extract’s the leather palm fruit (anthocyanin) to pH, pH range 0-5 with interval 1 obtained the best pH 1 with absorbance value 0,3965. Temperature stability test with temperature range 50 -100oC with 10oC range gives best temperature 50oC with absorbance value 0,387. The results of stability test of  pigment extract’s the leather fruit of palm (anthocyanin) to light showed decrease of absorbance value directly proportional to duration of irradiation The natural anthocyanin dye stability test derived from siwalan peel shows the extract with the greatest total anthocyanin having a large color intensity as well. Uji Stabilitas Zat Warna Alami  dari Limbah  Kulit buah Siwalan Buah siwalan (Borassus flabilifer) adalah salah satu buah lokal produk asli Indonesia yang dihasilkan dari tanaman lontar sangat melimpah karena tidak mengenal musim. Selama ini kulit buah siwalan masih belum banyak dimanfaatkan dan hanya dianggap sebagai limbah. Kulit buah siwalan mempunyai kandungan zat warna antosiaanin yang merupakan zat warna alami berwarna kemerah-merahan. Kulit buah siwalan di ekstraksi dengan menggunakan berbagai jenis solven antara lain air, campuran air etanol, campuran air – propanol, campuran air-etanol-propanol, etanol, campuran etanol – propanol dan propanol. Hasil ekstraksi terbaik didapatkan dengan menggunakan solvent etanol.  Selanjutnya dilakukan uji stabilitas ekstrak zat warna kulit buah siwalan (antosianin)  terhadap pH, suhu, sinar, dan warna dengan menggunakan spektrofotometer UV-Vis pada panjang gelombang maksimum 520 nm. Pada uji stabilitas ekstrak zat warna kulit buah siwalan (antosianin)  terhadap pH, rentang pH 0-6 dengan interval 1 didapat pH terbaik 1 dengan nilai absorbansi 0,3965. Uji stabilitas suhu dengan rentang suhu 50 -100oC dengan rentang 10oC menghasikan suhu terbaik 50oC dengan nilai absorbansi 0,387.  Hasil uji stabilitas ekstrak zat warna kulit buah siwalan (antosianin)  terhadap sinar menunjukkan penurunan nilai absorbansi berbanding lurus dengan lamanya penyinaran. Uji stabilitas zat warna alami antosianin yang berasal dari kulit buah siwalan menunjukkan ekstrak dengan total antosianin paling besar  memiliki intensitas warna yang besar pula.